Selection of a suitable standalone power supply system for an off-grid town in Western Australia - Ali, L.; Shahnia, Farhad (2016)
© 2016 IEEE.This paper focuses on selecting a suitable standalone power supply system for a small and remote off-grid town in Western Australia, Australia. To limit the cost of power supply system and to propose the most economically feasible solution for this town, different systems are considered. The considered systems, varied from a diesel-generator-based option towards a hybrid system composed of a diesel generator, wind turbine, a photovoltaic system and battery energy storage are analyzed by the help of HOMER software and using the real demand data of the town as well as the prices of different electrical components in the Australian market. The scenario which yields the minimum cost of energy and the minimum net present cost is defined and suggested. A sensitivity analysis is also performed to evaluate the impact of uncertainties of some of the parameters in the outcome of the study.